Academic and Administrative Issues for Implementation of Capstone Course in Civil Engineering programs: Case Study - María Fernanda Serrano-Guzmán; Diego Darío Pérez-Ruiz; Luz Marina Torrado-Gómez; Norma Cristina Solarte-Vanegas (Universidad Nacional, Costa Rica, 2017)
A capstone course is a culminating academic experience designed to encourage teamwork among students by applying their five years of classroom knowledge to solve realistic engineering problems. This emerging capstone experience demands academic and administrative changes to guarantee a satisfactory result within the time spared for this purpose. The main objective of this research is to assess students' perception regarding the capstone project as a culminating academic experience, and to use the analysis results to propose academic and administrative changes required to support and guarantee the successful achievement of this type of final degree project. To reach this goal, an assessment instrument was prepared and applied to 47 students enrolled in a capstone course. The instrument allowed collecting information regarding problem-based learning experience, teamwork experience, and self-perception concerning students' own behaviors and attitude during teamworking. On this regard, 87.2% of students considered capstone as a suitable final degree experience; however, it is challenging because it is known that student's participation during teamworking is uncommon and usually just two students are committed. In spite of this, 86.2% of students considered that teamwork was satisfactory and 95.2% of them recognized that their self-behavior and attitude during teamworking was good. Based on the results we recommend to strengthen teamwork strategies among students, and to instruct teachers about assessment strategies to evaluate individual and teamwork performance of students. It is expected that these findings can help improve the capstone curriculum related to courses and their administration. These findings are also supposed to serve as a previous experience to those universities committed to include capstone as a culminating degree experience.